The novel pleuromutilin derivative 22–((4-((4-nitrophenyl)acetamido)phenyl)thio)deoxy pleuromutilin possesses robust anti-mycoplasma activity both in vitro and in vivo - Xia, Xirui; Ji, Xuan; Li, Yaxi; Wang, Yubo; Zhao, Yue; Wang, Wenxiang; Ding, Huanzhong (Frontiers in Pharmacology, 2024)
ObjectiveMycoplasmas are structurally simple pathogenic microorganisms that can cause a wide range of diseases in humans and animals and conventional antibiotic therapies of fluoroquinolones and tetracyclines are toxic to young children and young animals and macrolide resistance is increasing. In this context, new anti-mycoplasma antimicrobial agents need to be developed. 22–((4-((4-nitrophenyl)acetamido)phenyl)thio)deoxypleuromutilin (compound 16C) is a novel acetamine phenyl pleuromutilin derivative. This study aimed to evaluate its acute toxicity in mice and generate pharmacokinetic and anti-mycoplasma profiles.MethodsThe safety of compound 16C was preliminarily evaluated by oral and intramuscular acute toxicity tests and single intravenous and intramuscular pharmacokinetic experiments were performed to obtain its pharmacokinetic profile. The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-killing curves reflected the in vitro effects of the compounds against Mycoplasma pneumoniae. Five groups consisted of three treatments for compound 16C (20, 40, and 80 mg/kg), and two treatments for tiamulin (oral and intramuscular 40 mg/kg) were continued for 4 d. Bronchoalveolar lavage fluid (BALF) and lung tissues were collected at the end of treatment (96 h) and 4 days later (192 h) to assess the in vivo anti-mycoplasma and anti-pneumonia effects. ELISA assays were performed to detect IFN-γ, TNF-α, and IL-8 (CXCL1) in BALF. Lung tissues were fixed with 4% paraformaldehyde and sectioned for histopathological assessment.ResultsThe results show that compound 16C has low toxicity (LD50 > 5,000 mg/kg). Its pharmacokinetic profile is characterized by a short time to maximum concentration (Tmax = 0.24 h), high bioavailability (F = 71.29%), and short elimination half-life (T1/2kel) (intramuscular and intravenous administration was 2.20 and 1.89 h, respectively). Treatment with compound 16C and intramuscular tiamulin reduced the mycoplasma load in mice. Intramuscular compound 16C and tiamulin also inhibited the release of IFN-γ, TNF-α, and CXCL1, decreasing the accumulation of inflammatory cells in the lungs, thereby mitigating lung damage.ConclusionThis study proved that compound 16C has a strong antimicrobial effect against M. pneumoniae, can be rapidly absorbed and has therapeutic efficacy that provides a basis for developing new anti-mycoplasma drugs.